STRATEGI KEBIJAKAN PEMERINTAH DAERAH JAWA BARAT TAHUN 2018-202 DALAM PENERAPAN PERATURAN DAERAH NO.3 TAHUN 20 - Syafira Subli Mahalmi; Robert Mubarrod (Jurnal Communitarian (Prodi Ilmu Politik), 2023)
Human trafficking is a problem that is happening more and more, and one of the ways that the West Java Regional Government is trying to prevent it is by issuing different policies. However, as of now, the problem has not been fully resolved. One of the reasons is that the policies that have been issued have not been properly implemented. Additionally, the quality of public officials needs to be improved, and more needs to help victims of human trafficking. Keywords: Government Policy. Human trafficking. Policy Implementation